Analysis of Base Monomer Elution from 3 Flowable Bulk-Fill Composite Resins Using High Performance Liquid Chromatography (HPLC) - Łagocka, Ryta (Med Sci Monit, 2018)
BACKGROUND: The aim of this study was to evaluate the elution of BisGMA, UDMA, TEGDMA, and HEMA monomers from flowable bulk fill composite resins with different resin matrix compositions, polymerized in 4-mm-thick layers, into 3 elution media. MATERIAL/METHODS: Three bulk-fill (SDR(®) (SDR), X-tra base (XB) and BEAUTIFIL-Bulk Flowable (BF)) resin-composites were tested. Cylindrical samples were immersed in 100% ethanol, 75% ethanol, and distilled water. The concentrations of the monomers were measured using the HLPC method (Agilent Technologies 1200 Series) after 1 and 24 h, as well as after 3, 7, 14, and 21 days. RESULTS: After polymerization of the tested resins, there was elution of the BisGMA, UDMA, TEGDMA, and HEMA monomers from the SDR and BF composites, but none of the tested monomers could be detected eluting from XB. The highest penetrations of the polymerized SDR and BF composites were observed in the 100% ethanol solution. This extraction medium eluted the highest amounts of free monomers. Some eluted monomers were not described in the composites Material Safety Data Sheets. CONCLUSIONS: The elution of the residual monomers depended on the resin composition and the materials filler/resin matrix ratio. In composite materials, toxicity assessment should be carried out, and should consider both the material composition as given by the manufacturer, and also the residual monomers that elute from the polymerized material. The elution concentration and time of monomers from composites depended on the solvent used. The highest penetrations of the polymerized SDR and BF composites were observed in the 100% ethanol solution, and this extraction medium eluted the highest amounts of free monomers. The 75% ethanol was a more aggressive medium than water in terms of monomer elution from bulk fill composites.